The Burden of Zoonoses in Kyrgyzstan: A Systematic Review. - Michel J Counotte; Gulnara Minbaeva; Jumagul Usubalieva; Kubanychbek Abdykerimov; Paul R Torgerson (PLoS Neglected Tropical Diseases)
Introduction Zoonotic disease (ZD) pose a serious threat to human health in low-income countries. In these countries the human burden of disease is often underestimated due to insufficient monitoring because of insufficient funding. Quantification of the impact of zoonoses helps in prioritizing healthcare needs. Kyrgyzstan is a poor, mountainous country with 48% of the population employed in agriculture and one third of the population living below the poverty line. Methodology/principal findings We have assessed the burden of zoonoses in Kyrgyzstan by conducting a systematic review. We have used the collected data to estimate the burden of ZDs and addressed the underestimation in officially reported disease incidence. The estimated incidences of the ZDs were used to calculate incidence-based Disability Adjusted Life Years (DALYs). This standardized health gap measure enhances comparability between injuries and diseases. The combined burden for alveolar echinococcosis, cystic echinococcosis, brucellosis, campylobacteriosis, congenital toxoplasmosis, non-typhoidal salmonellosis and rabies in Kyrgyzstan in 2013 was 35,209 DALYs [95% Uncertainty interval (UI):13,413-83,777]; 576 deaths [95% UI: 279-1,168] were attributed to these infections. We estimate a combined median incidence of ZDs of 141,583 cases [95% UI: 33,912-250,924] in 2013. The highest burden was caused by non-typhoidal Salmonella and Echinococcus multilocularis, respectively 14,792 DALYs [95% UI: 3,966-41,532] and 11,915 DALYs [95% UI: 4,705-27,114] per year. Conclusion/significance The health impact of zoonoses in Kyrgyzstan is substantial, comparable to that of HIV. Community-based surveillance studies and hospital-based registration of all occurrences of zoonoses would increase the accuracy of the estimates.